Operationalizing Inclusive Growth : Per-Percentile Diagnostics to Inform Redistribution Policies - Kireyev, Alexei; Leonidov, Andrei (Washington, D.C. : International Monetary Fund, 2020)
Inclusive growth, narrowly defined in this paper as growth that helps reduce inequality, is achieved if consumption of the poor increases faster than consumption of the rich. The paper presents a simple accounting framework for a per-percentile consumption diagnostics that could inform redistribution policies. The proposed framework is illustrated in application to Iraq and Tunisia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet